2020
DOI: 10.3389/fpsyg.2020.01656
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Differential Parenting: Study Protocol on a Longitudinal Study Investigating Child and Parent Factors on Children’s Psychosocial Health in Hong Kong

Abstract: Adolescents who believe that their parents treat them differently from their siblings have poorer psychosocial well-being than otherwise. This phenomenon, which is known as parental differential treatment or PDT occurs in up to 65% of families. Past studies have examined socio-demographic variables (e.g., child gender, age, and birth order) as predictors of PDT, but these immutable characteristics do little to inform interventions and help these adolescents. Hence, this study extends past research by investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…The partiality of the family to the second child may cause more complaints and problem behaviors of the firstborn child. 39 , 40 After 12 months of birth, the second child can move independently and walk in a small range. For various reasons, the child may be distracted by the activities of the second child, which interferes with the attention of the firstborn, and the older sibling’s craving for attention.…”
Section: Discussionmentioning
confidence: 99%
“…The partiality of the family to the second child may cause more complaints and problem behaviors of the firstborn child. 39 , 40 After 12 months of birth, the second child can move independently and walk in a small range. For various reasons, the child may be distracted by the activities of the second child, which interferes with the attention of the firstborn, and the older sibling’s craving for attention.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, official corruption makes individuals fell a sense of unfairness and inequality. According to the distributive and procedural justice theory, people evaluate the outcomes based on the quality of distributions and procedures, distributive and procedural justice are associated with satisfaction and wellbeing ( Tang and Baldwin, 1996 ; Lucas et al, 2011 ; Ng et al, 2020 ), individuals who perceived injustices of corruption would have lower wellbeing. Corrupt officials may distort the public resource allocations: they are likely to spend more on those who can provide larger benefits to them ( Liu and Mikesell, 2014 ), and there will therefore be less money to spend on public goods which are necessary for ordinary people.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…As mentioned earlier, parental traits (e.g., empathy) are considered important influences on child empathy development (Barnett et al, 1980;Eisenberg et al, 1989Eisenberg et al, , 1991Ng et al, 2020). Some twin studies have found that individual differences in infant empathy result from a confluence of genetic and environmental factors, which contain common elements related to parental empathy (especially maternal empathy; Volbrecht et al, 2007;Knafo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…During early childhood, empathy development relies on the progressive maturation of brain circuits and neural representations, constructed through interaction with the social environment (Dahl and Freda, 2017;Decety and Holvoet, 2021). Among family factors, scholars believe that parental dispositions (such as empathy), especially those of the mother (Fabes et al, 1990;Farrant et al, 2012), are related to infants' empathy development (Barnett et al, 1980;Eisenberg et al, 1991;Guo and Feng, 2017;Ng et al, 2020;Salvadori et al, 2021). Thus, excluding the influence of heredity, understanding the mechanisms through which parents' empathy influences children's empathy development would help provide caregivers with a clear practical framework and aid scholars in tracing the origins of individual differences in empathy during early childhood.…”
Section: Introductionmentioning
confidence: 99%